Investigation of in vitro antioxidant and cytotoxic potential of Triphala methanol extract in different ratios - Upoma, Shifat Sehrin Khan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.